Investigation of the effect of vacuum on the curing of mixtures on a silicate binder - O. A. Rusevich; S. L. Rovin (Литьë и металлургия, 2021)
The article presents the results of a study of the effect of vacuuming on the curing processes of liquid‑glass mixtures. The method of conducting experiments using an original laboratory vacuum installation and the mechanisms of curing a liquid‑glass mixture with various hardening methods are described. Studies have shown that vacuuming can signifi antly accelerate the curing and increase the strength of the mixture while reducing the content of the silicate binder. This; in turn; facilitates the knockability of liquid‑glass mixtures and expands the prospects for using these environmental friendly mixtures in foundry as an alternative to sands based on organic binders.